Textilepedia : the complete fabric guide. (Hong Kong : Fashionary International, 2021)
Textilepedia encompasses practical tips for a range of textiles with detailed visuals from deciphering different types of materials to understanding your finishing options A balance between text and imagery; it acts as a quick easy-to-navigate guide simplifying complicated fabric and fibre information using comparisons and relatable stories Whether you're a student or an industry veteran, Textilepedia is the complete guide you'll reach for throughout your career.
Keywords: Textiel